Antibacterial activity of a photosensitive hybrid cellulose fabric. Issue 11 (31st August 2018) - Ringot, Cyril; Saad, Naïma; Brégier, Frédérique; Bressollier, Philippe; Poli, Evelyne; Chaleix, Vincent; Ouk, Tan Sothea; Sol, Vincent
Abstract : A new photosensitive hybrid cellulose material, synthesized by polymerization of methacrylic acid (MAA) and PpIX, showed photoantibacterial activity against Staphylococcus aureus . Abstract : We report the preparation of a cellulose fabric bearing derivative protoporphyrin IX units covalently attached to the cellulose backbone of a fabric. Ce (IV) redox system radical polymerization was used to polymerize methacrylic acid (MAA) onto a cotton material and to obtain cotton- g -polyMAA. Attachment of the photosensitizer, a protoporphyrin IX (PpIX) amino derivative, on cotton- g -polyMAA was realized successfully by a classical peptidic covalent link. The modified surfaces were characterized by ATR-FTIR, DRUV, TGA, and SEM methods. Under visible light irradiation, protoporphyrinic cotton showed antibacterial activity against Staphyloccoccus aureus . This concept is very promising in the field of bacterial decontamination (sterile area, hospital equipment, etc .).